Impactos ecológicos do manejo comunitário de recursos naturais em comunidades ribeirinhas de várzea e terra firme na região de Tefé, AM - OLIVEIRA, Ana Cristina Mendes de (2011)
The theoretical bases of conservationism and preservation are discussed in this research, based on a field study carried out in the region of Tefé, the Middle Solimões. Twelve communities located in “Varzea” and “Terra Firme” ecosystems were studied, of which six communities have adopted a model of natural resourcemanagement, focusing on management of lakes and the other six have never participated in processes of management. The data of “Terra Firme” communities with and without management, not different from “Varzea” communities without management, in relation to perceptions of impact. The use of managed resources allowed greater control of them by the users. The model of management adopted was more appropriate to the communities in “Varzea” than in the communities of “Terra Firme”, according to the own characteristics of ecosystems.